Problem Based Learning Module in the Subject of Science, Hindu-Buddhist Kingdom Material - Dewi Mirayanti, Ni Luh; Suranata, Kadek; Yudiana, Kadek (Jurnal Pendidikan Multikultural Indonesia, 2024)
Science education in elementary schools is still partial and dominated by the use of textbooks, with teachers as the center of learning activities. The absence of teaching materials that support active student participation causes the learning process to be less meaningful. This study aims to develop and test the feasibility of a Problem Based Learning (PBL) module for science education for fourth grade elementary school students. This study uses a research and development method with the ADDIE model. Data collection techniques were conducted through observation, interviews, and questionnaires, while data analysis used a descriptive qualitative and quantitative approach. The validation results showed that the module was rated very good by subject matter experts (95%), learning design experts (95.45%), and media experts (98.3%). The teacher response test scored very good (100%), the individual trial (97.8%), and the small group trial (94.98%). These findings indicate that the module is highly valid and practical for use in learning. The uniqueness of this module lies in the integration of science and social studies material arranged contextually, for example, by linking the topic of Hindu-Buddhist kingdoms with the practice of planting crops by the ancient Javanese people. This study implies that the development of holistic and problem-based teaching materials can improve conceptual understanding and student engagement in IPAS learning.